The need to take into account the adsorption processes theory at the clinical and economic evaluation of the adsorption technologies (to the article «Clinical and Economic Evaluation of the Extracorporeal Blood Purification with Selective Sorption Techniques in ICU Patients) - A. A. Sokolov (Вестник анестезиологии и реаниматологии)
.